Sociology, Phenomenology, and Surrender-and-Catch - Wolff, Kurt H. (Synthese (Dordrecht), 1972)
Editorial Preface: This paper is far more "constitutive" (creative) than discursive. Abstracting it is committing an act of violation, & saying something about it in as narrow a space as an "abstract" provides is, at best, a compromise between opacity & distortion. However, by way of an abstract, taking seriously the Ed's invitation to contribute to an issue of Synthese "on the methodological situation in sociol & other soc sci's," the author found himself led to touch on aspects of the origin-validity & subject-object relations, of statements, of meaning, of meeting a crisis by "critical thinking," of the "natural att" & its "bracketing," thus of the diff between "leading a life" & "being," thence of "surrender & catch." The whole investigation comes to show itself to be an "occasion for surrender," in which the terms making up its title have become bracketed & in which those engaged in it have moved from the everyday world to the "world of suspension" & in the "catch," which also contains statements about sociol, once more into the everyday world. AA.